Brief Behavioral Treatment for Insomnia: A Meta-Analysis. Issue 6 (2nd November 2022) - Kwon, Misol; Wang, Jia; Wilding, Gregory; Dickerson, Suzanne S.; Dean, Grace E.
ABSTRACT: Purpose: The current study aims to quantify the effect of brief behavioral treatment for insomnia (BBTI) studies through meta-analysis. Method: Searches were performed from inception to February 2020, reporting on the effects of BBTI using randomized controlled trials (RCT) (adults aged 32 to 84). The main outcome measures were sleep onset latency (SOL), wake after sleep onset (WASO), sleep efficiency (SE%), and total sleep time (TST). Results: BBTI showed improved SOL compared with control group in mean difference at early (−15.42 [95% CI: −33.05 to −12.01; I2 =49%]) and late follow-up (-10.52 [95% CI: −1.12 to 0.54; I2=93%]). This was statistically significant at early follow-up, but not at late follow-up. The improvement of WASO by BBTI over the control group was shown at early follow-up (-17.47 [95% CI: −2.67 to 0.45; I2=90%]), and was statistically significant. For WASO, a non-statistically significant improvement of BBTI over the control group was shown at late follow-up (-12.77 [95% CI: −22.47 to -3.08; I2=0%]). SE% was shown improved statistically significant by BBTI over control group at early (4.47 [95% CI: −0.35 to 9.29; I2=98%]) and at late follow-up (6.52 [95% CI: −4.00 to 17.05; I2=89%]). The TST was shown no improvement by BBTI at early follow-up in mean difference (-2.97 [95% CI −38.83 to 32.90; I2=96%]). At late follow-up, TST was shown improvement in BBTI with mean difference (14.52 [95% CI: −31.64 to 60.68; I2=94%]) compared with the control group. Conclusion: Current evidence suggests that BBTI can be considered preliminarily efficacious and can be used for samples of middle-aged and older adults.